Traditional phytoremedies for the treatment of menstrual disorders in district Udhampur, J&K, India. (3rd February 2015) - Bhatia, Harpreet; Pal Sharma, Yash; Manhas, R.K.; Kumar, Kewal
Abstract: Ethnopharmacological relevance: Herbal remedies form an integral part of healing and are considered to be the oldest forms of health care known to mankind. The present study aims to document traditional phytoremedies for the treatment of menstrual disorders in Udhampur district of J&K, India. Material and methods: The informants were interviewed directly and information was gathered about plants used in different menstrual disorders. The data was further analyzed for use-value (UV), factor informant consensus ( F ic ) and fidelity level (Fl). Results: In all, 62 informants were interviewed. Most of the informants (66%) were females. The patients prefer female healers over male vaids and hakims . A total of 50 plants were used to cure different menstrual disorders. Seeds were found to be of utmost medicinal importance (43.8%) followed by leaves (20.8%) and fruits (16.7%). Oral administration was observed to be the main mode (90.0%) of intake of medicine. The plants with high use-value were Triticum aestivum (UV=1.76), Taraxacum officinale (UV=1.16), Citrus limon (UV=0.95), Allium cepa (UV=0.79), Cicer arietinum (UV=0.77), Trigonella foenum-graecum (UV=0.66), Rubia manjith (UV=0.56), Ocimum tenuiflorum (UV=0.56) and Oryza sativa (UV=0.52). The various menstrual disorders were classified into 7 categories. The values of F ic varied between 0.96 (dysmenorrhea, itching and foul smell) and 0.92 (menorrhagia). The 100% Fl value was scored by 20 plants. Leucorrhea reported the highest 5 plants with 100% Fl. Nearly 40% of the formulations had two or more plants. Conclusion: Plants used for the treatment of different menstrual disorders were documented and analyzed for ethnogynecological problems. The study revealed some plants like Triticum aestivum, Rubia manjith, Dalbergia sissoo, Raphanus sativus, Citrus limon, Allium cepa, Trigonella foenum-graecum, Elettaria cardamomum etc. to be of great importance vis a vis menstrual disorders. Further pharmacological studies of these plants may provide some important drugs for the treatment of common menstrual disorders. Graphical abstract: